Senegal : Fifth Review Under the Policy Support Instrument and Request for Modification of Assessment Criterion-Press Release; Staff Report. (IMF Staff Country Reports; Country Report, 2018)
This paper discusses Senegal's Fifth Review Under the Policy Support Instrument and Request for Modification of Assessment Criterion. Senegal's macroeconomic situation is stable. Growth is expected to exceed 6 percent in 2017 for the third year in a row, while inflation remains low. The fiscal deficit has been declining progressively in recent years and is projected to reach 3.7 percent of GDP in 2017. The current account deficit is projected to increase to 7.8 percent of GDP in 2017 owing to higher oil prices and slightly slower export growth. The outlook for the Senegalese economy remains on the whole positive. Senegal needs to continue implementing its structural reform program to maintain high growth rates of recent years.